Analysis of Voltage Sag Due to Short Circuit on the Sub System in Central Sumatera - Eteruddin, Hamzah; Hendry, Hendry; Atmam, Atmam (International Journal of Electrical, Energy and Power System Engineering, 2018)
Power quality is closely related to electrical energy which is directly related to voltage and current interference. Electrical equipment used daily requires good power quality. The thing that affects the quality of the power is the voltage dip. Based on the IEEE 1159-1995 standard, voltage sag is a decrease in RMS voltage with duration of 0.5 cycle to 1 minute. Sag voltage that occurs can have an effect on electronic equipment and other problems that often arise in the industrial environment. Therefore, a short circuit fault analysis was conducted to determine the voltage sag based on the type of fault in the sub system in Central Sumatera. Short circuit fault analysis is done using Powerworld Simulator 7.0 Students Edition. This study is intended to determine the sag voltage when there is a short circuit fault. The biggest voltage sag occurs when a short circuit fault of single phase to ground at 75% fault location and the smallest voltage sag when the three-phase short circuit of 0.7 fault location.